(untitled) (The Review of Diabetic Studies, 2024)
Hormones are intimately involved in the regulation of hematopoiesis, and many hematological functions are modulated by hormones. Circulating hormones and hematological functions must be viewed as part of an integrated process of physiological regulation. It remains uncertain whether these early observations of hematological irregularities should be considered merely pre-existing chronic conditions or subsequent complications of endocrine disorders. The immunological arsenal is under the influence of endocrine disorders, and in cases of cancer and viral infection, either the immunosurveillance outmatches the disease or the host succumbs due to immunological failure (Fernanda Pascutti et al., 2016) (Tsilingiris et al., 2022). Endocrine-hematological concomitants of oncological and virally infected patients draw considerable attention in the context of their clinical management.